Antidiscrimination Interventions, Political Ads on Transgender Rights, and Public Opinion: Results From Two Survey Experiments on Adults in the United States - Flores, Andrew R.; Haider-Markel, Donald P.; Lewis, Daniel C.; Miller, Patrick R.; Taylor, Jami K. (Frontiers in Psychology, 2021)
Political advertisements can shift attitudes and behaviors to become more exclusionary toward social out-groups. However, people who engage in an antidiscrimination exercise in the context of an experiment may respond differently to such ads. What interventions might foster inclusive attitudes in the presence of political communications about social policy issues like transgender rights? We examined two scalable antidiscrimination exercises commonly used in applied settings: describing a personal narrative of discrimination and perspective-taking. We then showed people political ads that are favorable or opposed to transgender rights to determine whether those interventions moderate how receptive people are to the messages. Relying on two demographically representative survey experiments of adults in the United States (study 1 N = 1,291; study 2 N = 1,587), we found that personal recollections of discriminatory experiences did not reduce exclusionary attitudes, but perspective-taking had some effects, particularly among those who fully complied with the exercise. However, both studies revealed potential backfire effects; recalling a discriminatory experience induced negative attitudes among a subset of the participants, and participants who refused to perspective-take when prompted also held more negative attitudes. Importantly, political ads favorable toward transgender rights consistently resulted in more positive attitudes toward transgender people. Future work needs to carefully examine heterogeneous responses and resistance to antidiscrimination interventions and examine what particular aspects of the political ads induced the attitude change.